The Republic of Poland at the Crossroads of Two Cultures (Politeja, 2017)
The Republic of Poland at the Crossroads of Two CulturesThe boundary of the Latin and Orthodox Church in the Piast times was a political border. These two boundaries fostered intensification of cultural differences. Christianity shaped the image of man, state, history, esthetic views as well as religious, social and political customs within two distinct cultures: Latin and Hellenic. On the Orthodox side, the patronage of faith in these areas was more unequivocal. In the times of the First Polish Republic both cultures met in one state. The political factor dominated in Latin American countries. It dictated the methods of action also to the Church. The conflict that was begun by the reign of Władysław Jagiełło and deepened by Sigismund III. Due to the Union of Brest, it triggered the conflict between Poland, Polish and Lithuanian Ruthenia and as a consequence – Moscow. The adaptation that Ruthenia had undergone in the Republic of Poland had far-reaching political, social, economic and cultural consequences. As a result of Moscow’s subsequent consolidation of Ruthenian lands, these processes affected all of these areas in the Moscow State. The conversion that occurred in the Republic of Poland on Ruthenian lands created a foundation for forming Ukrainian identity created by Austria. This fact is perceived in Russia as separatism used in geopolitical interests of many countries, including Poland, against Russia. Jagiellonian Poland that came to existence in the period of confessional tensions in Europe was subjected to internal contradictory cultural trends and political conflicts in the region, whereas Rome made efforts to control Christianity. These circumstances did not create prospects for development of the Republic of Poland.